Adherence to a standardized protocol for measuring grip strength and appropriate cut-off values in adults over 65 years with sarcopenia: a systematic review protocol. (October 2015) - Fox, Benjamin; Henwood, Tim; Schaap, Laura; Bruyère, Olivier; Reginster, Jean‐Yves; Beaudart, Charlotte; Buckinx, Fanny; Roberts, Helen; Cooper, Cyrus; Cherubini, Antonio; dell'Aquilla, Giuseppina; Maggio, Marcello; et al.
N/A: Review question/objective : The objective of this review is to examine the use of grip strength analysis in well and unwell populations in adults 65 years and over as a tool to establish muscle strength in sarcopenia. More specifically, the main review question is: 1. What protocol, if any, is most commonly used among older adults with sarcopenia and does this match the standardized protocol suggested in 2011 by Roberts et al.1? Secondary review questions are: 2. What are the reported cut‐off values being used to determine sarcopenia in older adults, with consideration for ethnic and gender variability? 3. Is grip strength, as a tool to measure muscle strength, suitable for people with common comorbidities and geriatric syndromes, such as osteoarthritis, often associated with sarcopenia? Background : Sarcopenia, a commonly used concept in geriatrics and gerontology, is characterized by a loss of muscle mass, muscle strength and/or physical functioning.1 Prevalence rates vary between 1‐39% in community dwelling older populations and 14‐33% in long‐term care populations.2 Several epidemiological studies have shown the association of sarcopenia with adverse health outcomes such as falls, disability, hospitalization and mortality.3‐4 Originally, sarcopenia refers to the loss of muscle mass with aging5, which was later complemented with loss of muscle strength and physical functioning. In 2010, the European Working Group on Sarcopenia in Older People (EWGSOP) reported a consensus definition of sarcopenia, which included measurement of low muscle mass and low muscle function (strength or physical performance).1 This consensus definition can be used to identify sarcopenia patients in clinical practice and to select individuals for clinical trials. Well‐designed clinical trials could ultimately lead to effective treatment and prevention strategies for sarcopenia. Since the publication of the consensus report, many studies have adopted this definition, which could potentially lead to better comparison of results between studies. On the other hand, within this definition there still is wide variability in measurement tools and use of cut‐off values, which could actually hamper comparability between studies. To assess muscle strength, the EWGSOP has recommended grip strength measurement which is easy and inexpensive. A recent systematic review on the measurement properties of tools to assess sarcopenia concluded that grip strength measurement is a valid and reliable method.6 In a comprehensive review of the measurement of grip strength in clinical and epidemiological studies by Roberts et al., 7 it was shown that there is wide variability in the choice of equipment and protocols for measuring grip strength. To enable comparison between studies, a standardized approach, incorporating more consistent measurement of grip strength is warranted. Based on the results of the review, a standardized approach was described7 including the utilization of the widely used Jamar hydraulic hand dynamometer, as was a clear assessment protocol. So far, it is unknown whether this approach has been adopted in studies investigating grip strength for sarcopenia. The primary aim of this current review is to identify whether studies are adhering to the suggested protocol, or whether a more common method is prevalent. The EWGSOP has suggested multiple cut‐off values to define sarcopenia regarding muscle strength: an absolute cut‐off score of 20 kilograms (kg) for women and 30 kg for men, 8 and Body Mass Index (BMI) specific cut‐off values for men and women.9 Alternatively, the Foundation for the National Institutes of Health (FNIH) Sarcopenia Study suggested cut‐off points of 26kg for males and 16kg for females, based on the likelihood of mobility impairment.10 Similar values have also been suggested by Dodds et al., 11 who generated grip strength reference values and calculated cut‐off points 2.5 standard deviations below the mean from 12 United Kingdom (U.K)based epidemiology studies. Recently, Beaudart et al.12 showed that large differences in sarcopenia prevalence occur when both cut‐off values are compared, especially in women.12 Additionally, prevalence has also shown to be dependent upon the tool used to assess muscle strength.13 Evidently, cut‐off values are highly varied and may be selected for statistical, theoretical or practical reasons, and/or are based on the type and magnitude of association with clinical endpoints such as hospitalization, falls or mobility. Difficulties arise in promoting a clear‐cut definition of sarcopenia with no consistent recommendation for cut‐off values of grip strength available. It is therefore important to identify which grip strength cut‐off values should be used for the identification of sarcopenia patients and how comorbidities such as osteoarthritis may affect such values. This review will aim to report on the cut‐off values used, the justification for and the considerations of comorbidities within the identified articles. Furthermore, a study has suggested that cut‐off values may be different within Asian populations. Therefore, ethnicity will also be taken into account for variations in appropriate cut‐off values.14 The overarching objective of this review is to provide insight into the current use of grip strength within the literature among older adults aged 65 and over and, subsequently, to provide commentary on the consistency of protocol and cut‐off values reported for grip strength measures. This insight into current research practice will lead to well‐considered recommendations concerning the measurement of grip strength in research and clinical practice. A preliminary search for sarcopenia revealed five systematic reviews in the Cochrane Library and two within the JBI Database of Systematic Reviews and Implementation Reports, but none that examine the protocol of grip strength measures. A single study was identified through a search of Medline [Via EBSCOhost] which examines the psychometric properties of common measures of muscle mass, strength and physical performance in sarcopenia6, but it was not specific to grip strength measures, nor did it examine the used protocol within studies. A lack of research into this area warrants further research and the need for the conduct of this proposed review.